Pathways and destinations of floating marine plastic debris from 10 major rivers in Java and Bali, Indonesia: A Lagrangian particle tracking perspective. (December 2022) - Iskandar, Mochamad Riza; Cordova, Muhammad Reza; Park, Young-Gyu
Abstract: Large amounts of plastic discharging from rivers in Java and Bali can potentially pollute many fishing areas in Indonesia. To identify strategies to mitigate this problem, it is important to understand the pathways and destinations of this marine debris. Therefore, the pathways and destinations of debris discharging from 10 major Java and Bali rivers were investigated using a Lagrangian particle tracking model. The amount of floating plastic discharging from each river was determined by the population in each river catchment area, the Mismanaged Plastic Waste ratio, and precipitation. Our study demonstrated that plastic debris pathways in Java and Bali primarily follow surface currents and are secondarily driven by wind toward the Indian Ocean. Around Indonesia, the prevailing monsoonal circulation plays an important role in determining the destination of floating debris. A larger amount of debris was discharged into the seas around Indonesia during the northwest winter monsoon when the precipitation rate was higher, leading to a considerable accumulation of debris in various Indonesian fisheries management areas. The areas most affected were Southern Java, Western Sumatra, and the Banda Sea in descending order. The most effect way of reducing the debris over Southern Java was reducing mismanaged plastic over Yogyakarta, Banten, and Bali provinces or along Progo River. Highlights: Lagrangian particle tracking was used to explore the fate of marine plastic debris originating from rivers in Java and Bali. The destination of the floating debris was mainly determined by prevailing monsoonal ocean circulation. Plastic debris was predominantly transported to the Indian Ocean. The northwest monsoon caused plastic debris to accumulate around Indonesia. The most affected fisheries management areas were Southern Java, Western Sumatra, and the Banda Sea.